2009
DOI: 10.1007/s00134-009-1561-x
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life decisions in an Indian intensive care unit

Abstract: Despite societal and legal barriers, half the patients dying in the ICU received a decision to limit therapy mostly as withholding or DNR orders. These decisions evolved early in the course of stay and resulted in significant reduction of therapeutic burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 36 publications
2
42
2
4
Order By: Relevance
“…Classically, the therapies most acknowledged as futile or useless are vasoactive drugs and dialysis methods. (14,15,(17)(18)(19)(20)(21)(22)(23) In the last years, the acceptance of withdrawing mechanic ventilation as a palliative ICU measures is growing. (9,24) Also is currently discussed the relevance of appropriate intensive care professionals' training in end-of-life patients management competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the therapies most acknowledged as futile or useless are vasoactive drugs and dialysis methods. (14,15,(17)(18)(19)(20)(21)(22)(23) In the last years, the acceptance of withdrawing mechanic ventilation as a palliative ICU measures is growing. (9,24) Also is currently discussed the relevance of appropriate intensive care professionals' training in end-of-life patients management competencies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the treating doctor has an obligation to ameliorate the patient's financial concerns by all means possible, including waiving of fees and involving other members of the health care team to help resolve the perceived problem. 11,20 When the patient is incompetent and NOK expresses financial concerns, the physician's obligation becomes to ensure that there is no conflict of interest between NOK's economic concerns and patient's benefit before withdrawing support.…”
Section: Withholding or Withdrawalmentioning
confidence: 99%
“…Intent will become a material consideration in such a case. 1,3,20 The distinction between suicide and euthanasia has been elucidated in the case of Naresh Marotrao Sakhre vs. Union of India (1994) where it has been held that, "Euthanasia or mercy killing is nothing but homicide whatever the circumstances in which it is effected. "…”
Section: Legal Aspects Of End Of Life Issues In Indiamentioning
confidence: 99%
“…Despite these barriers, a recent study from Delhi had reported that 49% deaths were preceded by EOL decisions. 5 The EIU, besides condemning India for poor palliative care system, also highlights Kerala as a successful model for the rest of world to follow. Kerala takes a uniquely community driven, holistic approach to EOL care.…”
Section: End Of Life Decision In Indian Armed Forces Hospitals Introdmentioning
confidence: 99%